Big Five Personality and Fear of Missing Out on Teenage Girls who Used Social Media - Nur Evira Anggrainy; Siti Aisa; Aris Soleman (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
This study aims to determine the relationship between the big five personalities and the fear of missing out (FoMO) in adolescent girls who use social media. In the big five personality variables, the research focused only on three personality traits, namely neuroticism, extraversion, and agreeableness. Meanwhile, two personality traits, namely openness to experience and conscientiousness, were not examined in this study. This type of research is quantitative, with the sampling technique using quota sampling. Research participants are female adolescents who live in Manado City, with an age range of 17 to 20 years, and have social media, with 222 participants. All participants who took part in this study used social media for over 3 hours per day. Data collection was done by distributing two types of questionnaires simultaneously and the questionnaire comprised a big five inventory and fear of missing out scales. The results showed that there was a significant relationship between the personality traits of extraversion and agreeableness with the fear of missing out on female social media users. While the neuroticism personality trait does not have a significant relationship.